Optimizing Teacher Engagement: The Role of Self-Efficacy, Interpersonal Communication, Organizational Culture, and Job Satisfaction Using Path and SITOREM Analysis - Ulfiah Hanum; Andi Hermawan (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Teacher engagement represents a teacher's alignment with their organization, characterized by physical, emotional, and rational commitment, fostering satisfaction and dedication to their profession. This study investigates strategies to enhance teacher engagement by analyzing the influence of self-efficacy, interpersonal communication, organizational culture, and job satisfaction. Employing a quantitative approach, the research uses path analysis to explore variable relationships and the SITOREM method to prioritize indicators for targeted interventions. Data were collected through surveys administered to 168 permanent teachers from PGRI vocational high schools in Bogor Regency, selected using the Slovin formula. The findings demonstrate that self-efficacy, interpersonal communication, and organizational culture significantly impact teacher engagement, both directly and indirectly, through job satisfaction. Organizational culture emerged as the most influential factor, highlighting the critical role of fostering a supportive, adaptive, and value-oriented work environment. SITOREM analysis identified actionable priorities, including enhancing teacher self-efficacy through vicarious experiences and verbal persuasion and strengthening organizational culture by promoting innovation and inclusivity. This study advances educational management by providing evidence-based recommendations for fostering teacher engagement. It underscores the necessity of integrating strategies that enhance individual capabilities and organizational dynamics to cultivate a motivated and committed teaching workforce. However, as the research is confined to vocational school teachers in one region, further studies are needed to validate and generalize these findings across diverse educational settings. Keywords: teacher engagement, self-efficacy, interpersonal communication, organizational culture, job satisfaction.